The dietary adequacy of organic vs conventional food consumers - Salvatori, Giancarlo; Forleo, Maria Bonaventura; Martino, Fabiana; Di Iuorio, Enrica; Piccinelli, Raffaela; Di Cesare, Cinzia (Progress in Nutrition, 2021)
Purpose - Aim of the article is to compare the diet of organic and conventional food consumers in order to assess whether their diet -both in terms of single component and as a whole diet- is balanced and how respectful it is compared to the reference levels for the Italian population.Design/methodology/approach - A sample of 110 Italian individuals was homogeneously categorized as Conventional, Organic-Weak and Organic-Strong consumers to assess and compare the nutritional adequacy of their diet. Food consumption was self-recorded on diaries structured by meal during three consecutive days in four different periods of the year specifying whether the food eaten was organic or not. A data management system developed by the Italian National Research Institute for Food and Nutrition was used to analyze data. The impact of eating habits on health was assessed by using a national-modified Healthy Food and Nutrient Index (iHFNI).Findings - Strong-organic subjects show significant higher caloric intake values but lower proteins and lipids compared with the conventional consumers. The diet of organic consumers, especially the strong ones, is characterized by a higher intake of dietary fiber, vitamins, minerals, and fruit and vegetables. A significant higher score of the iHFNI is measured for strong organic consumers. None of the groups shows improper eating habits and are especially away from national recommendations.Originality/value - First, the originality of the study remains in considering the nutritional profile, based on individual nutrients and on global food diets, together with the type of food consumption choices. Furthermore, rather than being based on a qualitative assessment, the collection of real consumption data based on a detailed diary, and the distinction between strong and weak organic consumers are essential to get more accurate results.